The global prevalence of anemia in patients with anorexia nervosa: a systematic review and meta-analysis - Salari, Nader; Razavizadeh, Sadaf; Abdolmaleki, Amir; Heidarian, Pegah; Rahimi, Avijeh; Shohaimi, Shamarina; Mohammadi, Masoud (BioMed Central, 2025)
Background: Anorexia nervosa (AN) is a mental disorder characterized by severe loss of appetite and low nutrient intake. Along with many complications, the anorexia nervosa eventually disrupts hematogenesis and the occurrence of anemia. Thus, the present study aimed to investigate the global prevalence of anemia in anorexia nervosa patient. Methods: Systematic searching was applied (by August 10, 2024) in databases of PubMed, Scopus, WoS, ScienceDirect, Embase, and the Google Scholar search engine. Selected investigations were imported to the EndNote Citation Management Software and duplicate papers were merged. Following consideration of inclusion and exclusion criteria (during primary and secondary screening) relevant papers were selected and underwent validation. Finally, eligible papers were selected for data extraction and meta-analysis (CMA v.2). The I2 index was used for heterogeneity assessment, and the Random Effect Model was used for meta-analysis. The results were categorized based on hematocrit and hemoglobin levels, and study type, and meta-regression was also applied for sample size and year of paper publication. Results: In the review of 9 eligible studies, the global prevalence of anemia in anorexia nervosa patient was found to be 44.8% (95%CI:25.7–65.7). Also, this value was detected in 48% (95%CI:19.9–77.4) and 43.4% (95%CI:18.6-72) based on hematocrit and hemoglobin levels, respectively. Meta-regression analysis showed that following the increase in sample size and year of paper publication, the global prevalence of anemia in Anorexia nervosa patient decreased and increased, respectively. Conclusion: A relatively high prevalence of anemia in individuals with anorexia nervosa requires proper attention to the regular blood monitoring and laboratory evaluations of the patients.